Management of critical risks to reduce death and disabled accidents Julcani mining unit - Molina Rosas, Marco Antonio (2023)
The objective of this research was to carry out the management of critical risks to reduce fatal and disabling accidents in the Julcani mining unit, period 2021-2022. The type of study was applied, non-experimental cross-sectional design of descriptive and explanatory correlational type; the sample consisted of 10 critical risks to which the workers of the Julcani Mining Unit are exposed daily; the data collection technique was observation through the observation guide instrument. Conclusion, during the last 48 years of mining in Peru, 96 fatal accidents were reported in the 1970s, a number that increased dramatically to 108 in the 1980s. However, after implementing SD. 055-2010 Memoria. The trend changed in 2010, with fewer fatalities and 26 fewer fatalities in 2018. Therefore that critical risk management reduces disabling and fatal accidents, we must emphasize that as an organization we must have identified which are the risks that can cause undesirable events of high potential, which must be analyzed and managed to preventively avoid any undesirable event that generates failures in the process.